The impact of digitalization and economic diversification on economic growth: evidence from Saudi Arabia - Neffati, Mohamed; Jbir, Rafik (Technological and Economic Development of Economy, 2024)
The present study aims to assess the impact of economic diversification and digitalization on economic growth in Saudi Arabia during the period 1990–2021. We have looked into this relationship in both the overall economic and non-oil economic sectors using the autoregressive distributed lag (ARDL) cointegration approach. The empirical results offer compelling evidence that economic diversification and digitization affect economic growth both directly and indirectly through their effects on non-oil GDP growth. The findings indicate that there is a long-run dynamic between economic growth, economic diversification, and digitalization. In the long run, digitalization contributes to the progress of non-oil economic growth and, therefore, sustainable economic growth. In addition, the causality test revealed that economic diversification develops the economy of new knowledge, which reinforces economic diversification, and non-oil economic growth supports digitalization. Consequently, digitalization played an important role in the Kingdom’s economic transition toward economic diversification. Indeed, our results prove that digitalization increases non-oil income and then reduces the supremacy of the oil sector in the economy, which promotes economic diversification. The KSA authority must accelerate the energetic transition process in order to support economic diversification and attract more foreign investment in information and communication technologies (ICTs).